1982
DOI: 10.1172/jci110561
|View full text |Cite
|
Sign up to set email alerts
|

Medullasin enhances human natural killer cell activity.

Abstract: A B S T R A C T Medullasin, a new serine protease found in bone marrow cells, increased markedly human natural killer cell activity. Whereas the natural killer cell activity measured immediately after the treatment with medullasin remained almost on the same level as the control, an incubation at 37°C for several hours increased markedly the natural killer cell activity of the lymphocytes treated with medullasin. Enhancement of the natural cytotoxicity was caused by the treatment with physiologic concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Conversely, the possibility that proteins released from neutrophil-derived granules might instead positively regulate NK cell functions was put forward by Aoki et al [28], who showed that neutrophil elastase can enhance NK cell activities by PBL toward K562 or Molt-4 cells. Subsequently, lactoferrin was shown to enhance the NK-mediated cytotoxicity and IL-2-induced LAK activity by PBLs [33].…”
Section: Figure 2 Schematic Depiction Of the Interactions Between Mumentioning
confidence: 99%
“…Conversely, the possibility that proteins released from neutrophil-derived granules might instead positively regulate NK cell functions was put forward by Aoki et al [28], who showed that neutrophil elastase can enhance NK cell activities by PBL toward K562 or Molt-4 cells. Subsequently, lactoferrin was shown to enhance the NK-mediated cytotoxicity and IL-2-induced LAK activity by PBLs [33].…”
Section: Figure 2 Schematic Depiction Of the Interactions Between Mumentioning
confidence: 99%
“… 20) Medullasin also plays important roles in the regulation of both immonity and nonspecific self defense mechanism (biophylaxis). It enhances human natural killer cell activity by causing the maturation of immature natural killer cells, 21) , 22) induces activated killer cells from CD16 positive cells which injure every malignant cell, 23) , 24) and increases DNA synthesis of human lymphocytes. 25) Medullasin also potentiates cytostatic activity and superoxide production of monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Medullasin has been shown to play an important role in biophylaxis. It induces in¯ammation by injuring endothelial cells in vessels (4), increases human natural killer cell activity (11), and activates both monocyte and lymphocyte functions (5). Therefore, it is possible that medullasin plays certain roles in causing clinical symptoms in multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%